AB0430 What is the role of ambulatory blood pressure monitoring in sle?. (23rd January 2014) - Er, E.; Akdogan, A.; Kilic, L.; Canpolat, U.; Kaya, B.; Karadag, O.; Kalyoncu, U.; Bilgen, S. A.; Kiraz, S.; Hayran, M.; Ertenli, I.
Abstract : Background: Patients with systemic lupus erythematosus (SLE) are at increased risk for the development of atherosclerotic cardiovascular disease (CVD). Hypertension (HT) which is frequently seen in SLE is a major risk factor for CVD. Ambulatory blood pressure monitoring is useful for both the diagnosis and the evaluation of HT. Objectives: This study was conducted to compare the results of office, home and ambulatory blood pressure monitoring measurements in SLE patients. Methods: We studied 86 SLE patients. Office, home and 24-hour ambulatory blood pressure measurements were performed in all patients. Results of the blood pressure measurements were evaluated according to current guidelines (1 ). Disease activity in SLE patients was defined by using the Safety of Estrogens in Lupus Erythematosus National Assessment-Sistemic Lupus Erythematosus Disease Activity Index (SELENA-SLEDAI) scores. Results: The mean age of the SLE patients (90.7% female) was 43±12 years. Of them 34 (39.5%) patients had a history of HT. In SLE patients with HT blood pressure control was not achieved in 12 (35.3%)patients with office measurements, in 16 (47.1%)patients with home measurements and in 13 (38.2%)patients with 24-hour ambulatory measurements. Among patients with no prior history of HT, there were 7 (13.5%)new diagnoses of hypertension by office measurements, 8 (15.4%)new diagnoses by home measurements and 9 (17.3%)new diagnoses by ambulatory monitoring. In the group with no prior history of HT, we observed that the concordance between the office and 24-hour ambulatory measurements was extremely low (Kappa: 0.116, p = 0.40). The concordance between self measurements at home and ambulatory measurements was moderate but less than ideally expected (Kappa: 0.504, p< 0.001). The results for patients with a history of HT were similar with Kappa values of 0.178 and 0.476 when comparing ambulatory measurements with office and home measurements, respectively. The SELENA-SLEDAI values for the concordant and discordant pairs were similar for both home versus ambulatory and clinic versus ambulatory comparisons (both p > 0.05, Mann-Whitney U test). Conclusions: The concordance between the blood pressure evaluation methods is low in SLE patients. 24-hour ambulatory blood pressure monitoring should be the preferred method for accurate evaluation of HT in patients with high risk for cardiovascular diseases. References: European Guidelines on cardiovascular disease prevention in clinical practice (version 2012): the Fifth Joint Task Force of the European Society of Cardiology and Other Societies on Cardiovascular Disease Prevention in Clinical Practice.2012;19(4):585-667. Disclosure of Interest: None Declared